Assessment of Groundwater Quality of Outer Skirts of Kota City with Reference to its Potential of Scale Formation and Corrosivity - Nitin Gupta; S. M. Nafees; M. K. Jain; S. Kalpana (E-Journal of Chemistry)
Kota City is a prominent industrial and educational town of Rajasthan state, India. Mega industrial projects of cement, fertilizers, power plant, oil seed processing units are located nearby the city. The groundwater of study area is used in domestic as well as in industrial activities. It is worthwhile to know the water quality status and its effect on entity, which is exposed in practical use. A comprehensive assessment of water quality parameters in groundwater samples drawn from 24 different locations, 6 sites from each direction at outer skirts of Kota City of Rajasthan, India, in four seasons of years 2006 to 2008 was carried out. To find out the suitability and stability of water, various indices available to assess the scale formation and corrosivity was used. The Langelier saturation index (LSI) and Ryznar saturation index (RSI) were calculated and discussed with respect to saturation level.